STUDENTS’ PERCEPTION ON THE USE OF VLOG IN FACILITATING STUDENTS’ SPEAKING SKILL IN SOLIHUDDIN SENIOR HIGH SCHOOL, THAILAND - Ahmad Farda Muzakki; Yani Awalia Indah (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2019)
This research aimed to find out students’ perceptions on the use of vlog in facilitating students’ speaking skill in Senior High School in Thailand. In conducting the research, the researcher used qualitative analysis. The researcher uses interview and questionnaire as research instrument. This research took students who understood technology in the Solihuddin School as the participants. Based on the data analysis, the result showed that the students’ perception on the use of vlog in facilitating students’ speaking skill is good. Students are more creative. They can create vlog in their speaking session. While creating vlog, students can study collaboratively. Students also can speak more confidently and fluently in practicing English speaking. Students are happy in creating a vlog because they are free to speak creatively and innovatively. Vlog can facilitate students in learning English speaking.